2019
DOI: 10.1021/acs.jpcc.9b08844
|View full text |Cite
|
Sign up to set email alerts
|

Porosity Development in Silica Particles during Polymerization: Effect of Solvent Reactivity and Precursor Concentration

Abstract: The porous morphology drives the application of nano-and mesoporous materials in a variety of areas. However, limited information is available on the porosity development during their synthesis at various times due to challenges in experimental and simulation techniques. In this work, we have probed the porosity development in silica particles using Monte Carlo simulation techniques. We have developed an algorithm to measure the porosity of small, irregular shaped, finite-size particles formed during the polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…To understand the effect of the initial concentration of silica precursor (C SiP ) on the ring formation behavior, we have probed two systems with R = 20 and R = 2, which correspond to C SiP = 104 and 155 mg cm À3 (henceforth referred to as dilute silica (DS) and concentrated silica (CS) systems), respectively. In our recent work, 68 we observed that the silica system with C SiP lower than 104 mg cm À3 does not result in larger silica clusters within the simulation timescales, whereas, at C SiP = 155 mg cm À3 , all of the silica precursors react to form one giant cluster and the rate of silica polymerization is faster compared to the other systems studied.…”
Section: Simulation Detailsmentioning
confidence: 61%
See 4 more Smart Citations
“…To understand the effect of the initial concentration of silica precursor (C SiP ) on the ring formation behavior, we have probed two systems with R = 20 and R = 2, which correspond to C SiP = 104 and 155 mg cm À3 (henceforth referred to as dilute silica (DS) and concentrated silica (CS) systems), respectively. In our recent work, 68 we observed that the silica system with C SiP lower than 104 mg cm À3 does not result in larger silica clusters within the simulation timescales, whereas, at C SiP = 155 mg cm À3 , all of the silica precursors react to form one giant cluster and the rate of silica polymerization is faster compared to the other systems studied.…”
Section: Simulation Detailsmentioning
confidence: 61%
“…However, the development of the algorithms for silica polymerization and their verification are discussed in detail in our previous work. 65,68 The developed algorithms successfully capture the kinetics of silica polymerization and the evolution of rings, clusters, and porosity during polymerization. 65,68 To report our observations with respect to real-time, we scaled the simulation time (i.e., MC steps) with appropriate scaling factors calculated from the kinetic model of silica polymerization (discussed in detail in our recent work 68 ).…”
Section: Simulation Detailsmentioning
confidence: 99%
See 3 more Smart Citations